# Trigonometric rule on a spherical square

Consider a square on a sphere (in three dimensions), with edges of length $a$ and angles $\beta$. I want to prove the following formula: $$\cos(a) = \cot^2(\beta /2) = \frac{1 + \cos(\beta)}{1 - \cos(\beta)},$$ but I have no idea how to do this, and which (spherical) rules I can use.

Given a spherical square whose side length is $a$ and vertex angle is $\beta$. Draw one of the diagonals (this diagonal will bisect the vertex angles) & call the length of this diagonal $x$, this will split the square into two isoceles triangles. Consider one of these trianlges, it will have lengths $a,a,x$ and opposite angles $\beta/2, \beta/2, \beta$ respectively. By the sine rule we have
\begin{eqnarray*} \frac{\sin(x)}{\sin(\beta)} =\frac{\sin(a)}{\sin(\frac{\beta}{2})} \\ \sin(x) = 2 \sin(a) \cos(\frac{\beta}{2}). \end{eqnarray*} Now apply the cosine rule (using the diagonal as the base) \begin{eqnarray*} \cos(x)=\cos^2(a)+\sin^2(a) \cos(\beta) \\ \cos(x)=1-2\sin^2(a) \sin(\frac{\beta}{2}). \end{eqnarray*} Square the above equation & Pythagorus ... we have \begin{eqnarray*} \sin^2(x)=4 \sin^2(a) \sin^2(\frac{\beta}{2})(1-\sin^2(a) \sin^2(\frac{\beta}{2})). \end{eqnarray*} From the sin rule we can eliminate $x$ ... we have \begin{eqnarray*} \cos^2(\frac{\beta}{2})= \sin^2(\frac{\beta}{2})(1-\sin^2(a) \sin^2(\frac{\beta}{2})) \\ \sin(a)=\frac{-\cos(\beta)}{\sin^4(\frac{\beta}{2})}=\frac{-4 \cos(\beta)}{(1-\cos(\beta))^2} \end{eqnarray*} Now pythagorus, square root & we are done \begin{eqnarray*} \color{red}{\sin(a)=\frac{1+\cos(\beta)}{1-\cos(\beta)}} = \color{blue}{\cot \left( \frac{\beta}{2} \right)}. \end{eqnarray*} Perhaps the nicest example of a square project onto the surface of a sphere is a cube ...

In this case the vertex angle is $\beta =\frac{ 2 \pi}{3}$ and the edge length angle is $a=\cos^{-1}(\frac{1}{3})$.

Let $a$ be a side of the square, $b$ be a diagonal, and $\beta$ be a vertex angle. Draw both diagonals, which bisect and are perpendicular to each other. Apply the spherical Pythaorean Theorem to any of the four triangles thus formed:

$\cos a = (\cos(b/2))^2=(1+\cos b)/2$

$\cos b =2\cos a-1$

Now apply the Law of Cosines to one of the larger triangles formed by just one diagonal:

$2\cos a-1 = \cos^2 a + \sin^2 a \cos \beta$

Subtracting $\cos^2 a$ and using standard identities gives

$-(1-\cos a)^2 = (1+\cos a)(1-\cos a) \cos \beta$

Cancel out the common factor $(1-\cos a)$ and then solve for $\cos a$ to get:

$\cos a = \frac{1+\cos \beta}{1-\cos \beta}=\frac{2\cos ^2 (\beta/2)}{2\sin ^2 (\beta/2)}=\cot ^2 (\beta/2)$

Consider the diagram

Using the Spherical Law of Cosines, we get $$\cos(\rho)^2=\cos(\alpha)\tag{1}$$ Then the Spherical Law of Sines says \begin{align} \frac{\sin^2(\alpha)}{1} &=\frac{\sin^2(\rho)}{\sin^2(\beta/2)}\\ &=\frac{1-\cos(\alpha)}{\sin^2(\beta/2)}\tag{2} \end{align} Therefore, \begin{align} \sin^2(\beta/2) &=\frac{1-\cos(\alpha)}{\sin^2(\alpha)}\\ &=\frac1{1+\cos(\alpha)}\tag{3} \end{align} Thus, \begin{align} \cos(\alpha) &=\csc^2(\beta/2)-1\\[5pt] &=\cot^2(\beta/2)\\ &=\frac{1+\cos(\beta)}{1-\cos(\beta)}\tag{4} \end{align}